2013
DOI: 10.1007/s13762-013-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of biosorbents and copper sequestration from simulated wastewater

Abstract: This paper reports the potential of chemically treated wood chips to remove copper (II) ions from aqueous solution a function of pH, adsorbent dose, initial copper (II) concentration and contact time by batch technique. The wood chips were treated with (a) boiling, (b) formaldehyde and (c) concentrated sulphuric acid and characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and energy dispersive analysis X-ray. pH 5.0 was optimum with 86.1, 88.5 and 93.9 % copper (II) removal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…hydroxide, sulphide or chelating precipitation, as well as ion-exchange or adsorption (Wan Ngah et al 2002;Akar et al 2009;Zhu and Li 2015;Jain et al 2016), e.g. with activated carbon, carbon nanotubes, magnetic nanoparticles (Feitoza et al 2014), low-cost adsorbents from industrial waste streams (Castaldi et al 2015;Cretescu et al 2015) or bioadsorbents (Davis et al 2003;Deng et al 2013;Hokkanen et al 2013;Shaheen et al 2013;Bansal et al 2014;Ş en et al 2015;Komkiene and Baltrenaite 2016). Furthermore, membrane filtration processes (Ujang and Anderson 1996;Qdais and Moussa 2004) such as ultrafiltration, nanofiltration, reverse osmosis or electrodialysis are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxide, sulphide or chelating precipitation, as well as ion-exchange or adsorption (Wan Ngah et al 2002;Akar et al 2009;Zhu and Li 2015;Jain et al 2016), e.g. with activated carbon, carbon nanotubes, magnetic nanoparticles (Feitoza et al 2014), low-cost adsorbents from industrial waste streams (Castaldi et al 2015;Cretescu et al 2015) or bioadsorbents (Davis et al 2003;Deng et al 2013;Hokkanen et al 2013;Shaheen et al 2013;Bansal et al 2014;Ş en et al 2015;Komkiene and Baltrenaite 2016). Furthermore, membrane filtration processes (Ujang and Anderson 1996;Qdais and Moussa 2004) such as ultrafiltration, nanofiltration, reverse osmosis or electrodialysis are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum percent desorption of Pb(II) and Cd(II) of 78% and 71% were, respectively, achieved within 1 h for HCl concentration of 0.05 M from NaOH activated Irvingia gabonensis, as shown in Figure 1 adsorbent surface was covered with H and Cd(II) ions were disrupted. Thereafter, the metal ions could not compete with H exchange sites and subsequently heavy solution [19]. …”
Section: Desorption Resultsmentioning
confidence: 99%
“…It can be observed that the removal of nickel increases with increasing time in the first 0.5 h and thereafter the removal is not significant, indicating that the minimum contact time necessary for a good heavy metal removal is 0.5 h. This indicates that the maximum removal of nickel is achieved within 0.5 h after which concentration of nickel in the solution become constant. This may be explained by the fact that initially for adsorption large number of vacant sides was available, which slowed down later due to exhaustion of remaining surface sites and repulsive force between solute molecule and bulk phase 36,37 . The rapid removal of the adsorbate has significant practical importance as it will facilitate smaller reactor volumes ensuring efficiency and economy [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
Section: Resultsmentioning
confidence: 99%